Potential Cost-Effectiveness of Pneumococcal Conjugate Vaccine (PCV) in Turkey - (:unkn) unknown (ELSEVIER SCIENCE INC, 2013)
Background: Pneumococcal infection is an important and preventable cause of morbidity and mortality. The Turkish government introduced 7-valent pneumococcal conjugate vaccine (PCV) into the national immunization program in 2009. This suggests that replacing 7-valent PCV with a higher-valent version could at least maintain standard of care if not improve it, and that it could be affordable. Objectives and Methods: The aim of this analysis was to assess the potential direct cost-effectiveness of 13-valent PCV in Turkey, a country with a birth cohort of 1.4 million, against a no vaccine state, against the default 7-valent PCV state, and against a 10-valent PCV state, using a published cohort model with a 5-year horizon. Results and Conclusions: The cost per life-year gained is below the 1 x per-capita gross domestic product threshold across large changes in key input parameters, indicating that the model is stable and suggesting that any PCV would be very cost-effective in a Turkish national pediatric immunization schedule.
Keywords: burden of disease; children; cost-effectiveness; pneumonia; vaccines; ACUTE OTITIS-MEDIA; STREPTOCOCCUS-PNEUMONIAE; HAEMOPHILUS-INFLUENZAE; CHILDREN YOUNGER; PROTEIN-D; DISEASE; IMMUNIZATION; MENINGITIS; PREVENTION; EFFICACY